In Wakefield's laboratory: Tangata Whenua into property/labour in Te Waipounamu. (June 2020) - Barber, Simon
This article follows the alchemical political economy of Edward Gibbon Wakefield for whom Kāi Tahu whenua served as a laboratory. Wakefield's clever formula for the transubstantiation of an incendiary social situation in Britain into new terrain for capital was designed to secure the transplantation of English economic and social relations to the colonies to ensure the persistence of a landless class compelled to sell their labour for wages. Ingeniously, the transport of that labour to the colonies was to be paid for by the market in land in the new colony: Kāi Tahu would be made to fund their own colonisation. I track the fate of capital's settler dream for ready land and labour as it was brought into being by the New Zealand Company, subsequently taken over by the Crown, and as it continues into our present. The argument is divided into two parts. The first is the classical moment of primitive accumulation, clearing people from the land to provide a market in land and labour, 'legal' dispossession, and commodification. The second is the more recent continuation of the initial processes of dispossession and commodification as these assert themselves in processes of redress and as they are expressed in the corporatisation of Ngāi Tahu.